3D Analysis Of The Hip Joint For The Prediction Of Osteoarthritis - Burkov, Ilya Sergeevieh (St. Edmunds College, 2019)
Hip osteoarthritis is an increasingly important cause of morbidity in the ageing population causing pain, disability and loss of function through joint failure. It has an estimated lifetime risk of 25%. While the contribution of skeletal morphology to disease is now established, the lack of imaging biomarkers that can reliably predict osteoarthritis development is limiting. Novel biomarkers for clinically relevant hip osteoarthritis are needed particularly methods to identify patients who are destined for total hip replacement (THR) surgery and who might benefit from novel interventions. The chosen techniques studied here involved 2D and 3D measures of hip cortical bone structure from routine clinical computed tomography (CT) scans of patients to predict clinically-relevant hip osteoarthritis. Outside the research environment, clinical practice and trials still use simple 2D outcome measures from radiographs. Clinical diagnosis and surgical decision making therefore rely on combinations of poorly-defined disease signs and symptoms and controversially, 2D radiographic imaging. Such methods overlook key 3D disease features. In many osteoarthritis guidelines, clinicians are now advised to avoid imaging altogether. This work asked three important research questions concerning hip osteoarthritis. 1. Does imaging have clinical utility in managing patients with hip pain, and in particular are hip radiographs effective in predicting THR? 2. Does 3D imaging using clinical CT have clinical utility in predicting THR, and is there a 3D phenotype of bone thickening associated with eventual THR? 3. Is the 3D bone thickening associated with hip osteoarthritis an inevitable consequence of ageing? In order to answer these, CT cortical thickness data was acquired from two population based studies; one in only older men and women from the Age, Gene/Environment Susceptibility- Reykjavik (AGES) Study in Iceland and the other from the Mindways study acquired from 11 healthcare centres around the USA, of women aged 20-97 years. CT ...